ChemInform Abstract: Synthesis of Cyclooctatetraenes Through a Palladium‐Catalyzed Cascade Reaction. Issue 42 (September 2016) - Blouin, Sarah; Gandon, Vincent; Blond, Gaelle; Suffert, Jean
Abstract: A unique pathway for the synthesis of fully substituted cyclooctatetraenes is developed using Pd‐catalyzed cyclization of trialkynyl derivatives in the presence of tributyltin organyls.